2022
DOI: 10.1177/21582440221123200
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Social Enterprise Research: A Systematic Literature Review

Abstract: Given the noteworthy contribution to the global socio-economic development, research on social enterprises (SE) has gained prominence over past two decades. Making a clear departure from for-profit counterparts, the core purpose of SEs is to deliver a social mission while at the same time staying financially viable and as a consequence, “sustainability” is strongly embedded in their core drive of existence. Rapidly sprouting body of literature on SE posits that “sustainability” is intensely coincided with “soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Leadership is affirmed in many studies as one of the antecedents driving sustainability in SE [1]. There is a tension in managing SE as one of the goals is to deliver an impact to society whereas the second goal is to create a sustainable business that is financially successful.…”
Section: Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Leadership is affirmed in many studies as one of the antecedents driving sustainability in SE [1]. There is a tension in managing SE as one of the goals is to deliver an impact to society whereas the second goal is to create a sustainable business that is financially successful.…”
Section: Leadershipmentioning
confidence: 99%
“…According to Kantabutra's study on SEP and leadership [47], a leader ought to have a clarity of vision for abstraction, challenge, and future orientation. The vision must comprise moderation, reason, the need for a self-immunity mechanism, knowledge, and morality imagery that is directly associated with sustainable employment and customer satisfaction, and with a satisfactory financial outcome [1]. Another study by Phukamchanoad [62] confirmed that the leader in a community should be committed to the application of SEP in order live a life of sufficiency.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al, 2021b). To integrate sustainability into SIP operational management is not only the entry point for theoretical research and application of scientific and technological resource allocation and scientific research management, but also the actual demand and management challenge for sustainable development of most current social organizations (Jayawardhana et al, 2022). Although SIPs are different from social enterprises and supported by government annual financial grants, SIP sustainability reveals a fresh but ongoing problem and challenge for contemporary organizational management and business models capable of transforming the social landscape of science, technology and the market economy.…”
Section: Introductionmentioning
confidence: 99%
“…The result of implementing green practices in various business entities is their gradual greening. The indicated greening process is observed by researchers at least on the example of the activities of social enterprises (Davies, Mullin, 2011;Jayawardhana et al, 2022;Withisuphakorn, 2017). These entities are a rather specific type of business entity, as their purpose of operation is primarily to achieve the set social goals, and not to maximize the profits made.…”
Section: Introductionmentioning
confidence: 99%